2021
DOI: 10.14238/pi61.1.2021.20-4
|View full text |Cite
|
Sign up to set email alerts
|

Preterm human milk composition and dietary intake of breastfeeding mothers in the Indonesian population

Abstract: Background Human milk consumption is a protective factor against infection. However, the high variability of human milk composition makes it difficult for clinicians and researchers to assess the adequacy of nutritional intake. Objective To identify the nutritional profiles and composition of premature human milk and dietary intake of breastfeeding mother. Methods Human milk specimens were collected from mothers who gave birth to very premature and/or very low birth weight infants. Infants had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Studies in Indonesia for protein intake in lactating women showed varied results, with most of the studies indicating a protein intake of 70% RDA. Recently, Marsubrin et al ( 54 ) showed a decline in protein intake during the 4-week of lactation (64.6–57 g; 80.8–71.3% RDA).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in Indonesia for protein intake in lactating women showed varied results, with most of the studies indicating a protein intake of 70% RDA. Recently, Marsubrin et al ( 54 ) showed a decline in protein intake during the 4-week of lactation (64.6–57 g; 80.8–71.3% RDA).…”
Section: Resultsmentioning
confidence: 99%
“…In Indonesia, energy intake among lactating women ranged from 1,482 to 2,556 kcal (55.9–96.5% RDA). Marsubrin et al ( 54 ) demonstrated a decreasing energy intake among lactating women through the weeks with an intake of <80% RDA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low birth weight infants cause significant neonatal morbidity and mortality events. Preterm labour is a major threat worldwide for mothers who are experiencing pregnancy; preterm labour can occur if the baby is born less than 32 weeks or weighs less than 1,500 grams (Marsubrin, Rohsiswatmo, & Sjarif, 2021).…”
Section: Introductionmentioning
confidence: 99%